Introduction to Roundtable Discussion: Nora Jaffary’s Reproduction and Its Discontents in Mexico - Dyck, Erika (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2018)
The following is a brief introduction to the papers that accompanied the roundtable discussion for the Ferguson Prize Winner. The recipient in 2018 was Nora Jaffary’s Reproduction and its Discontents in Mexico: Childbirth and Contraception from 1750 to 1905.